2016
DOI: 10.3791/53628
|View full text |Cite
|
Sign up to set email alerts
|

<em>Ex Vivo</em> Optogenetic Dissection of Fear Circuits in Brain Slices

Abstract: Optogenetic approaches are now widely used to study the function of neural populations and circuits by combining targeted expression of light-activated proteins and subsequent manipulation of neural activity by light. Channelrhodopsins (ChRs) are light-gated cation-channels and when fused to a fluorescent protein their expression allows for visualization and concurrent activation of specific cell types and their axonal projections in defined areas of the brain. Via stereotactic injection of viral vectors, ChR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…5C and Fig.S5). The electrophysiological and morphological properties of mICC neurons in our studies matched previously described properties of mICC neurons [15][16][17].…”
Section: Ex Vivo Optogenetic Stimulation Of the Bma-icc Pacapergic Pasupporting
confidence: 85%
See 1 more Smart Citation
“…5C and Fig.S5). The electrophysiological and morphological properties of mICC neurons in our studies matched previously described properties of mICC neurons [15][16][17].…”
Section: Ex Vivo Optogenetic Stimulation Of the Bma-icc Pacapergic Pasupporting
confidence: 85%
“…We wanted to determine if altering the activity of PACAPergic neurons that innervate the mICCs changes fear behavior. A previous study showed that the ex vivo optogenetic method can be used to analyze and study the role of intercalated cells in regulating fear behaviors, so we utilized optogenetics to answer our question [16]. For these experiments, we used the Adcyap1-2A-Cre mice and carried out the same intersectional virus labeling strategy described previously.…”
Section: Intersectional Viral Methods For Expressing Chr2 Specificallymentioning
confidence: 99%
“…9. Make a skin incision of approximately 1 cm on top of the head using scissors 20 ( Figure 1B,E) and a hinged "double replica table" (see Figure 3B), which when opened produces a tensile fracture through the frozen specimen (Figure 2). This allows to retain and replicate both sides of the fractured specimen.…”
Section: Protocolmentioning
confidence: 99%
“…Murine hippocampal organotypic slice cultures were prepared as previously described [50]. After one week in culture the slices were treated for 24 or 48 h with ISCADOR Qu, Aviscumine, and native ML-1 or were left untreated.…”
Section: Methodsmentioning
confidence: 99%